The role of immunohistochemistry for diagnosing undifferentiated malignancy in the head and neck region (BIRDEM Medical Journal, 2019)
Background: Undifferentiated tumours in the head and neck region are not uncommon. They can arise from different sites like in mucosa as well as in salivary glands, soft tissues or lymph nodes. Histopathological examination plays a central role in the diagnosis but difficulties arise with some tumours which are poorlydifferentiated due to their high inter- and intra-observer variability. In those cases, immunohistochemistry has greatly assisted to diagnose the tumours that cannot be accurately identified using routine histopathological procedures. The correct histopathological diagnosis is essential especially in case of malignant tumourwhere subsequent specific therapy is required. The aim of this study was to determine the role of immunohistochemistry for diagnosing undifferentiated malignancy in the head and neck region.Methods: This cross-sectional study was conducted during July 2014 to June 2015. A total of 35 Bangladeshi patient’s specimens of head and neck swelling were collected from two renowned laboratories in Dhaka city.These cases were diagnosed as undifferentiated tumour in histopathological examination.Standard protocol was followed for immunohistochemistry.Then primary immunohistochemical panel which included the markers for Epithelial CK (AE1/AE3),mesenchymal marker (Vimentin) and lymphoid marker (LCA) were used.The cases which were not resolved by primary immunohistochemistry panel, the second panel was applied for further sub classification (Desmin, Chromogranin, CK20, CEA, CD20, CD30, HMB45, NSE). Based on interpretation of immunohistochemical findings final diagnoses were made.Data analysis was performed using the Statistical Package for the Social Sciences for Windows version 22.0 (SPSS, Chicago, Illinois, USA).Results: A total of 35 undifferentiated tumorsof head-neck region were studied.The mean age was 46.3±17.6 years and male to female ratio was 4.8:1. The majority 13 (37.1%) patient had cervical lymphadenopathy, 11 (31.4%) had neck mass and 4(11.4%) had in nasal/sinonasal mass.Regarding histopathologicalcell types, round cell was 21 (60.0%), spindle cell 6 (17.1%), pleomorphic cells 6(17.1%) and epithelioid cells 2(5.7%). In initial histopathological examination, majority 25(71.4%) were undifferentiated malignant neoplasm, 8(22.8%) were metastatic undifferentiated carcinoma, 1(2.9%) was pleomorphic sarcoma and the remaining 1(2.9%) had malignant adnexal tumour. By application of immunohistochemistry, most (33, 94.3%) of the cases were resolved and the two cases remained unresolved. Among the resolved cases majority (15, 45.5%) were lymphoma, 4(12.1%) were metastatic carcinoma, 3(9.1%) were Ewing’s sarcoma and malignant melanoma were found in 3(9.1%) cases.Conclusion: This study supports that the immunohistochemical technique has a fundamental role in the investigation of undifferentiated tumour origin, to determine the correct guidance for treatment and improving the prognosis for head and neck tumour patients.Birdem Med J 2020; 10(1): 48-53